Prognostic indicators for failed nonsurgical reduction of intussusception - Jiraporn Khorana (2018)
© 2016 Khorana et al. Purpose: To identify the risk factors for failure of nonsurgical reduction of intussusception. Methods: Data from intussusception patients who were treated with nonsurgical reduction in Chiang Mai University Hospital and Siriraj Hospital between January 2006 and December 2012 were collected. Patients aged 0-15 years and without contraindications (peritonitis, abdominal X-ray signs of perforation, and/or hemodynamic instability) were included for nonsurgical reduction. The success and failure groups were divided according to the results of the reduction. Prognostic indicators for failed reduction were identified by using generalized linear model for exponential risk regression. The risk ratio (RR) was used to report each factor. Results: One hundred and ninety cases of intussusception were enrolled. Twenty cases were excluded due to contraindications. A total of 170 cases of intussusception were included for the final analysis. The significant risk factors for reduction failure clustered by an age of 3 years were weight <12 kg (RR =1.48, P=0.004), symptom duration >3 days (RR =1.26, P<0.001), vomiting (RR =1.63, P<0.001), rectal bleeding (RR =1.50, P<0.001), abdominal distension (RR =1.60, P=0.003), temperature >37.8°C (RR =1.51, P<0.001), palpable abdominal mass (RR =1.26, P<0.001), location of mass (left over right side) (RR =1.48, P<0.001), poor prognostic signs on ultrasound scans (RR =1.35, P<0.001), and method of reduction (hydrostatic over pneumatic) (RR =1.34, P=0.023). The prediction ability of this model was 82.21% as assessed from the area under the receiver operating characteristic curve. Conclusion: The identified prognostic factors for the nonsurgical reduction failure may help to predict the reduction outcome and provide information to the parents.